Metastatic smooth muscle tumor of uncertain malignant potential after laparoscopic presuming myomectomy - Marisa Tossamartvorakul; Marie Christine Valerie R. Mendoza; Kuan- Gen Huang; Shu- Han Chang (Wolters Kluwer Medknow Publications, 2021)
A 38-year-old para-2 female underwent laparoscopic myomectomy with uncontained morcellation. Three years later, she complained of epigastric pain. An intraperitoneal 3 cm mass beneath the umbilicus was showed on computed tomography (CT) scan. With the impression of gastrointestinal stromal tumor, she underwent open laparotomy at the general surgery department. A tumor was excised. Pathological examination showed that the tumor was consistent with a smooth muscle tumor of uncertain malignant potential smooth muscle tumors of uncertain malignant (STUMP). Six years postlaparoscopic myomectomy, during a regular follow-up, three parauterine masses were found on ultrasonography and CT scan. She underwent laparoscopic surgery for hysterectomy, bilateral salpingectomy, and excision of the masses. The masses were again diagnosed as STUMP. This case presents a recurrence of a rare type of smooth muscle tumor after uncontained morcellation. If myomas are to be removed with morcellation, it should only be used appropriately with a compatible containment system, and the risk of occult malignancy should be counseled.